Sub-millimetre wave imaging - Dahlbäck, Robin (My University, 2011)
The sub-millimetre wave region withholds many interesting properties that can be used for imaging. Common packaging materials are transparent making package inspection possible without the use of ionising radiation. Contrast can also be seen between healthy and diseased tissue for some common forms of cancer. Many other biomedical applications are still un- explored making it an interesting research topic. A study of common system topologies are presented together with an imaging system built with in-house components. The imaging system is adopted for the use of a microwave to- mography image reconstruction algorithm. System characterisation data are presented, the usable bandwidth is 6.5 % centred around 337 GHz. Mea- surement repeatability and long therm stability is also evaluated, concluding that the system most likely is good enough for use with the image recon- struction algorithm. Furthermore test images are presented.
Keywords: Livsvetenskaper; Grundläggande vetenskaper; Elektronisk mät- och apparatteknik; Bioanalytisk teknik; Life Science; Basic Sciences; Electronic measurement and instrumentation; Bioanalytical engineering